Die saalklerk as hulppersoneellid in 'n akademiese hospitaalverplegingseenheid - T. van der Merwe; M. Muller (AOSIS, 1993)
The expectation (knowledge and insist) of unit managers as well as ward clerks regarding the duties and responsibilities of the ward clerk in an academic hospital nursing unit in Johannesburg, were questioned. The value of a structured educational programme for ward clerks in order to improve their capabilities profile (knowledge and insist) was also examined. The expectations (knowledge and insight) of unit managers in academic hospital nursing units where ward clerks were employed, were poor regarding the duties and responsibilities of such ward clerks.